Surgical Repair of an Atraumatic Avulsion of Patellar Tendon at the Tibial Tuberosity in an Adult Patient - Lorenzo Maria Di Giacomo; M. Shahid Khan; Michele Bisaccia; R. Rende; G. Rinonapoli; A. Caraffa (Case Reports in Orthopedics)
Atraumatic avulsion of the tibial attachment of patellar tendon in adults is a very rare injury with only few published case reports. Here we are sharing the successful management and follow-up of a similar case with a different suture material for repair of the tendon, the FiberWire. We believe that the management we are discussing allows for early return to activity with good functional outcome.